2022
DOI: 10.1111/ctr.14596
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 pandemic on the size of US transplant waiting lists

Abstract: Background More patients are waitlisted for solid organs than transplants are performed each year. The COVID‐19 pandemic immediately increased waitlist mortality and decreased transplants and listings. Methods To calculate the number of candidate listings after the pandemic began and short‐term changes that may affect waiting time, we conducted a Scientific Registry of Transplant Recipients surveillance study from January 1, 2012 to February 28, 2021. Results The number of candidates on the liver waitlist cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Due to reduced transplant center activity initially in certain areas of the country, there may have been fewer exception cases being listed; in addition, deaths due to COVID-19 before or after transplant could have influenced waitlist and transplant outcome metrics for the postpolicy era. [7][8][9] Beginning on June 28, 2022, the median transplant score for exception cases is based on transplants performed within 150 nm from the donor hospital, rather than 250 nm around the transplant hospital. This would not have affected the current analysis, but the effects of this change remain to be seen, and outcomes after this policy will continue to be monitored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to reduced transplant center activity initially in certain areas of the country, there may have been fewer exception cases being listed; in addition, deaths due to COVID-19 before or after transplant could have influenced waitlist and transplant outcome metrics for the postpolicy era. [7][8][9] Beginning on June 28, 2022, the median transplant score for exception cases is based on transplants performed within 150 nm from the donor hospital, rather than 250 nm around the transplant hospital. This would not have affected the current analysis, but the effects of this change remain to be seen, and outcomes after this policy will continue to be monitored.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 was declared a national emergency in the United States on March 13, 2020, meaning that most of the postpolicy era occurred in the context of COVID-19. Due to reduced transplant center activity initially in certain areas of the country, there may have been fewer exception cases being listed; in addition, deaths due to COVID-19 before or after transplant could have influenced waitlist and transplant outcome metrics for the postpolicy era 7–9 …”
Section: Discussionmentioning
confidence: 99%
“…24 Moreover, studies have also reported increased waitlist removals due to mortality during the initial phases of the COVID-19 pandemic, which may also reflect higher mortality rates among older adults awaiting KT. 65…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al utilized Scientific Registry of Transplant Recipients (SRTR) data to examine waitlist trends from 2012 to 2021. 1 The heart and liver transplant waitlists had been declining prior to 2020, while the kidney and lung waitlists remained roughly unchanged from 2018 to 2020. All waitlists shrunk in the first half of 2020 because of COVID-19.…”
Section: Covid-19mentioning
confidence: 99%